2020
DOI: 10.3390/polym12091921
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Cross-Linked Graphene Oxide on Polyethersulfone Membrane for Pharmaceuticals and Personal Care Products Removal

Abstract: The unique two-dimensional structure and chemical properties of graphene oxide (GO) provide a convenient method for preparing novel membranes. In this study, GO membranes were prepared through filtration by a pressure-assisted self-assembly method involving the cross-linking of three diamine monomers on a polyethersulfone (PES) support. The different small molecular diamines, ethylenediamine, butanediamine, and p-phenylenediamine, were introduced as cross-linking agents to investigate the effect of diamine on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 53 publications
(56 reference statements)
1
4
0
Order By: Relevance
“…Although other authors have worked at different pH values, in this work the experiments were carried out under conditions of neutral pH due to the isoelectric properties of the contaminant and the membranes used. However, values of permeate flows and rejection coefficients similar to those obtained in this study can be found [34][35][36].…”
Section: Ibuprofen Removalsupporting
confidence: 86%
“…Although other authors have worked at different pH values, in this work the experiments were carried out under conditions of neutral pH due to the isoelectric properties of the contaminant and the membranes used. However, values of permeate flows and rejection coefficients similar to those obtained in this study can be found [34][35][36].…”
Section: Ibuprofen Removalsupporting
confidence: 86%
“…However, other reports indicate no significant improvement [ 28 ] or even deterioration of the examined properties [ 27 ]. In the papers where 100% removal of the tested PPCPs was achieved [ 29 ], different membrane techniques were used than in this study. Table 4 presents a comparison of performance of different membranes used for PPCP removal.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, numerous authors modified membranes to make the membrane processes more effective for these substances. Cellulose acetate nanofiltration membranes modified by charged molecules were investigated [ 26 , 27 ] and similar modifications were made on ultrafiltration membranes made of poly(ether sulfone) [ 28 , 29 ]. Such modifications improved the separation properties of membranes in relation to many PPCPs type compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-covalent functionalization involves the binding of molecules via supermolecular interactions, including π–π stacking and electrostatic interaction. 92 Non-covalent modification of graphene does not have any effect on its structural properties, thereby preserving inherent properties. Noble metals [such as gold (Au), silver (Ag), platinum (Pt)], metal oxides, biomolecules (hemoglobin, cytochromes), have some excellent electrocatalytic properties and graphene in combination with these nanostructures has been used to further optimize electrochemical sensing of NO.…”
Section: Graphene-based Electrochemical Sensorsmentioning
confidence: 99%